COMPARED EFFICACY OF INTRA-ARTICULAR INJECTION OF METHYLPREDNISOLONE AND TRIAMCINOLONE - Abdul Fettah Buyuk (Acta Ortopédica Brasileira, 2017)
Objective: To compare the effect of two different corticoste - roid types in bilateral and symmetrical knee osteoarthritis (OA). Methods: One hundred and twenty-six patients received injections of methylprednisolone acetate (MP) in one knee and triamcinolone hexacetonide (TH) in the contralateral knee. Patients were evaluated before injection and 2, 4, 8, 12, and 24 weeks after. Results: Mean patient age was 68.5±9 years. Mean BMI was 26.3±2.6 kg/m 2 . At first admission, mean VAS score was 7.7±1.3 for the right side and 7.5±1.5 for the left side, and mean WOMAC score was 67.6±14.4. After bilateral intra-articular injection, VAS scores for both knees and WOMAC scores decreased significantly when initial scores were compared with 2, 4, 8, 12, and 24 weeks after injection (p<0.05). A statistically significant change was seen over time when VAS and WOMAC scores for 2, 4, 8, 12, and 24 weeks post-injection were compared to each other (p<0.05). No significant difference was seen between knee sides (p>0.05). Conclusion: MP and TH have similar efficacy in relieving pain and improving function. The efficacy of intra-articular corticosteroid injection peaks 2 weeks after injection and the effect continues until the 24 th week. Level of Evidence II, Comparative Pro - spective Study.